Attitude towards assisted reproductive technology: acceptance of donors eggs, sperms, and embryos as treatment of human infertility: a systematic review and meta-analysis - Dereje Bayissa Demissei; Tolesa Diriba Biratu; Eriste Nigussa Gamshe; Ababe Tamirat Deressa (BMC, 2024)
Abstract Introduction Assisted Reproductive Technology utilizes human sperm, eggs, or embryos in vitro to produce pregnancy. However, there is no evidence of the acceptance of these technologies by the community. Objective This study aimed to determine the pooled prevalence of positive attitudes toward the acceptance of donor eggs, embryos, and sperm. Methods The protocol was registered in PROSPERO (number: CRD42022348036). The Condition, Context and Population (CoCoPop) protocol of the systematic review was used to address the relevant questions regarding the objective of the study. Data were extracted into Excel and pooled estimates were calculated using STATA Version 16. Results The pooled prevalence of positive attitudes toward accepting donor eggs, embryos, and sperms was 38.63%, 33.20%, and 31.34%, respectively. Subgroup analysis revealed that the pooled prevalence of positive attitudes toward accepting donor eggs was high in non-Asian countries (47.78%) and among infertile men (38.60%). Similarly, the pooled prevalence of positive attitudes toward accepting donor eggs was high in non-Asian countries (47.78%) and among infertile men (28.67%). However, the pooled prevalence of positive attitudes toward accepting donor sperm was high in non-Asian countries (37.6%) and among infertile women (28.19%). Conclusion The pooled estimate of the prevalence of positive attitudes toward accepting donor eggs was higher than the prevalence of positive attitudes toward accepting donor embryos and sperm. Infertile men and non-Asian countries have a higher prevalence of positive attitudes toward accepting eggs and embryos, whereas non-Asian countries and infertile women present a higher prevalence of positive attitudes toward accepting donor sperm. Therefore, regulatory bodies and policymakers should modify their rules and regulations to ensure the availability of minimum standards for the ethical and safe practice of donor conception as a treatment for infertility at national and international levels.